2021
DOI: 10.1155/2021/6640652
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Screening Identifies Prognostic Long Noncoding RNAs in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy with a poor prognosis. Therefore, there is an urgent call for the investigation of novel biomarkers in HCC. In the present study, we identified 6 upregulated lncRNAs in HCC, including LINC01134, RHPN1-AS1, NRAV, CMB9-22P13.1, MKLN1-AS, and MAPKAPK5-AS1. Higher expression of these lncRNAs was correlated to a more advanced cancer stage and a poorer prognosis in HCC patients. Enrichment analysis revealed that these lncRNAs played a crucial role in HCC progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…LncRNA NRAV has been reported to be involved in the antiviral immune response ( 73 , 74 ). In addition, several independent bioinformatics analyses have demonstrated that it is a valuable clinical prognostic biomarker in HCC ( 75 , 76 ) and lower-grade glioma ( 77 ). ZFPM2-AS1 is reported to be involved in numerous tumors, including lung adenocarcinoma ( 78 ), renal cell cancer ( 79 ), gastric carcinoma ( 80 ) and HCC ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NRAV has been reported to be involved in the antiviral immune response ( 73 , 74 ). In addition, several independent bioinformatics analyses have demonstrated that it is a valuable clinical prognostic biomarker in HCC ( 75 , 76 ) and lower-grade glioma ( 77 ). ZFPM2-AS1 is reported to be involved in numerous tumors, including lung adenocarcinoma ( 78 ), renal cell cancer ( 79 ), gastric carcinoma ( 80 ) and HCC ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may help explain why many successful preclinical responses are not reproduced after entering real clinical trials. In addition, compared with other studies using the TCGA database to develop lncRNA prognostic models (13)(14)(15)(16)(17)(18), our HCCSenLncSig model is comparable. This shows that the senescent cells in the TME are helpful in predicting the prognosis of HCC, and are at least as valuable as other biomarkers.…”
Section: Discussionmentioning
confidence: 83%
“…A high level of LINC00958 aggravated HCC lipogenesis and progression through sponging miR-3619-5p, further upregulating the hepatoma-derived growth factor expression (12). Although several lncRNA prognostic models for HCC have been developed (13)(14)(15)(16)(17)(18), the potential immune microenvironment predictive ability and therapeutic guidance of the models, especially for immunotherapy, have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…AC099850.4 is one of the top lncRNA in miRNA-lncRNA network and may be associated with tumor division, tumor proliferation, cell cycle and so on in ovarian cancer (Zhao et al, 2020). Higher expression of NRAV was associated with advanced clinical stage, poor prognosis and immunologic characteristics in hepatocellular carcinoma patients (Feng et al, 2021;Xu et al, 2021). However, to date, there are few studies on these lncRNAs in hepatocellular carcinoma under hypoxia.…”
Section: Discussionmentioning
confidence: 99%